2009
DOI: 10.4314/ajbr.v9i3.48897
|View full text |Cite
|
Sign up to set email alerts
|

Catheter associated urinary tract infection: Aetiologic agents and antimicrobial susceptibility pattern in Ladoke Akintola University Teaching Hospital, Osogbo, Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
19
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
13
19
1
Order By: Relevance
“…Biofilm producer strains were resistant to penicillin (86.7%), gentamicin (66.7%), tetracycline (65.3%), and ciprofloxacin (60%), whereas the rate of resistance to these antibiotics in biofilm non-producers was much lower, consistent with previous reports [15,27,28]. In line with other performed studies, the antimicrobial resistance rate was higher in biofilm-producing S. aureus isolates than in non-biofilm producers [9,12,15,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Biofilm producer strains were resistant to penicillin (86.7%), gentamicin (66.7%), tetracycline (65.3%), and ciprofloxacin (60%), whereas the rate of resistance to these antibiotics in biofilm non-producers was much lower, consistent with previous reports [15,27,28]. In line with other performed studies, the antimicrobial resistance rate was higher in biofilm-producing S. aureus isolates than in non-biofilm producers [9,12,15,29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The high percentage of significant bacteriuria recorded is consistent with similar observations elsewhere (Bonadio et al, 2001;Bonadio et al, 2005). Although, in this study, the culture positive rate reported is higher than 51% reported from South Africa (Habte et al, 2009), 43.3% from Ethiopia (Teshager et al, 2008), 30% from Nicaragua (Matute et al, 2004) and 39% from India (Kothari and Sagar, 2008), it was lower than the 88.5% culture positive rate reported in a study carried out within the same geographic environment as our hospital (Taiwo and Aderounmu, 2006). This can be explained by the differences in the population studied such as mean age, pre-morbid state and the reasons for admission.…”
Section: Discussionsupporting
confidence: 89%
“…Koshariya and colleagues reported the prevalence of CABUTI in India to be 27% [22]. In Nigeria, Taiwo et al reported the prevalence of CABUTI of 13.3% and 98.8% when bladder catheter was in situ at less than 7 days or more than 7 days respectively [23]. In this study, the prevalence of CABUTI was 72.1%.…”
Section: Discussionsupporting
confidence: 45%